Weak Laws of Large Numbers of Cesaro Summation for Random Arrays - Tran, Manh Cuong (H.: ĐHQGHN, 2015)
In this paper, we establish weak laws of large numbers with or without random indices for Cesaro summation for random arrays of random elements in Banach spaces. Our results are more general and stronger than some well-known ones. AMS Subject classification 2000: 60B11, 60B12, 60F05, 60G42.